2020
DOI: 10.1021/acsnano.0c07569
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Spin-Selective Transport in Chiral Metal–Organic Crystals with Temperature-Activated Magnetization

Abstract: Room-temperature, long-range (300 nm), chirality-induced spin-selective electron conduction is found in chiral metal–organic Cu(II) phenylalanine crystals, using magnetic conductive-probe atomic force microscopy. These crystals are found to be also weakly ferromagnetic and ferroelectric. Notably, the observed ferromagnetism is thermally activated, so that the crystals are antiferromagnetic at low temperatures and become ferromagnetic above ∼50 K. Electron paramagnetic resonance measurements and density functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
88
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(96 citation statements)
references
References 62 publications
(91 reference statements)
5
88
0
Order By: Relevance
“…As the Cu(I/II)–ligand vibration(s) proceeds, it generates charge displacements in the chiral ligand’s electron cloud, and these are accompanied by partial spin polarization of the electron cloud. 51 Because the amplitude of the motion is small at low temperature and is nearly harmonic, the local fluctuating B vib field is small. At higher temperatures ( Figure 4 B), larger displacements occur along the vibrational coordinate, and they access more anharmonic regions of the vibrational coordinate between the copper and its chiral ligands, giving rise to a net local magnetic polarization.…”
Section: Resultsmentioning
confidence: 99%
“…As the Cu(I/II)–ligand vibration(s) proceeds, it generates charge displacements in the chiral ligand’s electron cloud, and these are accompanied by partial spin polarization of the electron cloud. 51 Because the amplitude of the motion is small at low temperature and is nearly harmonic, the local fluctuating B vib field is small. At higher temperatures ( Figure 4 B), larger displacements occur along the vibrational coordinate, and they access more anharmonic regions of the vibrational coordinate between the copper and its chiral ligands, giving rise to a net local magnetic polarization.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work, these crystals were shown to have good conduction and both ferromagnetic and ferroelectric properties at room temperature. 13 As a demonstration of their material properties, we showed that this material can be used to fabricate spintronic devices with multilevel memory 34 as well as a spin transistor device. 35 This spin transistor device also exhibits nonlinear memristive behavior utilized as a universal memory, and it enables logic operations.…”
mentioning
confidence: 94%
“…It was previously found that conduction through the crystals is spin selective at room temperatures, due to the CISS effect. 13 In that reference, the coercive field is measured at different temperatures and was found to be about 200 Oe at room temperatures. Since the excitation by circularly polarized light results in exciting in a one spin direction, following the excitation, there is an electron in the excited state with one specific spin and the hole in the ground state has the same specific spin.…”
mentioning
confidence: 99%
“…Chirality [14] has recently been used in designing new chiral catalysts [15], developing organic spin filters [16], and investigating spin-dependent tunnelling through chiral molecules [17][18][19]. It has an important role in photochemistry that may have been important in the origin of life [20].…”
Section: Introductionmentioning
confidence: 99%